Membentuk dan Mengembangkan Kultur Positif Sekolah dengan Cara Menerapkkan Manajemen Berbasis Kelas - Rita Armaiyetti (Pedagogi: Jurnal Ilmu Pendidikan, 2019)
The paper describes the best practice experience of the author to manage school to establish and develop a positive culture of school empowering school resources by implementing Class-Based Management of human resources in Sekolah Dasar Negeri 38 Payakumbuh. Positive cultures relate to the time, discipline, cleanliness, learning, and embarrassment culture, of class members. The positive culture was developed into school culture. The result is changes in attitudes and personalities of school residents, conductive school climate, learners centered, and the increase of creativity of learners. Key to the success of Dedication, Effort, Initiative, Transparency, Prayer, Organizing, Loyalty, Activity, and Reflection, abbreviated DUIT POLAR.